2005
DOI: 10.1097/01.tp.0000174131.47469.d2
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus and Tacrolimus Trough Concentrations and Dose Requirements after Kidney Transplantation in Relation to CYP3A5 and MDR1 Polymorphisms and Steroids

Abstract: Unlike tacrolimus, sirolimus adjusted trough concentrations and dose requirements seem not affected by CYP3A5 and MDR1 polymorphisms. Adjusted-prednisone dose has a significant impact on tacrolimus and sirolimus dose requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(69 citation statements)
references
References 34 publications
5
61
1
2
Order By: Relevance
“…Two studies found an effect of the CYP3A5*1 allele on SRL exposure. However, it was specifically in patients without CNI cotreatment (5,6 ), but this was not confirmed in a third study (7 ). In the study we report here, in which the number of patients was relatively large compared to those in previous studies, the results are not in favor of this effect either, despite the fact that patients received no CNI cotreatment, which may have concealed the genetic effect.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Two studies found an effect of the CYP3A5*1 allele on SRL exposure. However, it was specifically in patients without CNI cotreatment (5,6 ), but this was not confirmed in a third study (7 ). In the study we report here, in which the number of patients was relatively large compared to those in previous studies, the results are not in favor of this effect either, despite the fact that patients received no CNI cotreatment, which may have concealed the genetic effect.…”
Section: Discussioncontrasting
confidence: 51%
“…There is currently no evidence supporting an influence of polymorphisms of the gene ABCB1 [ATP-binding cassette, sub-family B (MDR/TAP), member 1] 8 (the P-gp-encoding gene) (4 ) on SRL pharmacokinetics and clinical outcomes in kidney transplant patients. On the other hand, controversial results have been published concerning the impact on SRL exposure of polymorphisms of the gene CYP3A (cytochrome P450, family 3, subfamily A) (5)(6)(7). The CYP3A5*3 allele (rs776746 AϾG), which results in a truncated enzyme (8 ), has been associated with higher SRL blood concentrations in kidney transplant recipients.…”
Section: © 2013 American Association For Clinical Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the data in literature is controversial. While there were studies showing reduced oral bioavailability of sirolimus in CYP3A5 expressors (Anglicheau et al, 2005;Le Meur et al, 2006), similar association was not found in other studies (Mourad et al, 2005;Renders et al, 2007). Moreover, none of the studies could show the influence of ABCB1 genotype on sirolimus exposure (Anglicheau et al, 2005;Mourad et al, 2005;Renders et al, 2007).…”
Section: Mammalian Target Of Rapamycin Inhibitorsmentioning
confidence: 73%
“…Such results have been reported previously in the literature concerning this polymorphism. [5][6][7][8][9][10] A previous study by Patel and associates studied the effect of CYP3A5 polymorphism on tacrolimus drug dosing in North Indian renal allograft recipients. 11 To our knowledge, the present study is the first study to show the association between CYP3A5 genetic polymorphism and tacrolimus drug level in a South Indian population.…”
Section: Discussionmentioning
confidence: 99%